Marco Damiani (2016), La Sinistra radicale in Europa. Italia, Spagna, Francia, Germania [The Radical Left in Europe. Italy, Spain, France, Germany], Roma: Donzelli - Daniela Chironi (Coordinamento SIBA, 2017)
For Book Reviews abstract is not required